PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN PERTAMBANGAN DALAM PERSPEKTIF TEORI AGENSI (Studi Empiris Pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2017-2019) - Tita Prastya Puspita; Moh. Amin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study was to determine whether there is an influence on company characteristics, namely company size, profitability, company profile, number of commissioners, and leverage on the disclosure of corporate social responsibility. The sample used in this study is 60 mining companies listed on the Indonesia Stock Exchange from 2017 to 2019 with information on disclosure of corporate social responsibility and a summary of financial data obtained through annual reports of mining companies. The sample collection technique was done by using purposive sampling method and data management was carried out using multiple linear regression analysis. The results of this study indicate that the size of the company, the company profile, and the number of the board of commissioners have an influence on the disclosure of corporate social responsibility. Meanwhile, on the other hand, profitability and leverage have no effect on disclosure of corporate social responsibility.Keywords: Size, Profitability, Company Profile, Number of Commissioner, and Leverage